Recurrence of gastric cancer in patients who are disease-free for more than 5 years after primary resection - Lee, Ju-Hee; Kim, Hyun-Il; Kim, Min Gyu; Ha, Tae Kyung; Jung, Min-Sung; Kwon, Sung Joon (Surgery, 2016)
Late recurrence of gastric cancer is rare and there are few data on recurrence in patients who are disease free for >5 years after gastrectomy. The aim of this study was to evaluate the predictors and status of tumor recurrence among these patients. Clinicopathologic characteristics, patterns of recurrence, and postrecurrence survival were analyzed in patients who were diagnosed as disease free at 5 years postoperatively and thereafter experienced recurrence. Independent factors associated with the late recurrence were analyzed. Among 1,573 patients who underwent curative surgery from June 1992 to December 2006, 348 patients had recurrence. Of them, 7.6% (n = 25) suffered from late recurrence after 5 years after gastrectomy. Among patients who were diagnosed as disease free at 5 years after surgery, it accounted for 2.8% (25/902). Cases with late recurrence were characterized by more aggressive clinicopathologic features than those without recurrence. The median time to recurrence was 88.8 months (range, 64.8–238.0); of the 25 patients, 18 (72.0%) had recurrence within 8 years after surgery. The most common pattern was peritoneal recurrence (n = 19; 76.0%). The estimated median survival after recurrence was 9.4 months. On multivariate analysis, pT4 classification was the only independent risk factor for late recurrence. There were 185 patients with pT4 tumor who had no recurrence at 5 years after surgery; 19 (10.3%) had late recurrence. pT4 tumor was the only important predictor of late recurrence. Whether extended follow-up for T4 tumors affects survival needs to be demonstrated in more large-scale studies.